Spectral relationships of Carleman integral equation in some different domains - El Rahman, R.O. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, the potential theory method (PTM) is used, in some different domains, to obtain the solution of Fredholm integral equation (FIE) of the first kind with Carleman kernel. The solution is obtained in the form of spectral relationships (SRs). Many new and important relationships are established and discussed from the work.